2004
DOI: 10.1002/anie.200400661
|View full text |Cite
|
Sign up to set email alerts
|

Methods for the Chemical Synthesis of Fullerenes

Abstract: C(60) has been synthesized by chemical methods in 12 steps. Lessons learned in the author's laboratory during a decade devoted to the synthesis and study of open geodesic polyarenes strongly influenced the strategy and methodology ultimately employed for preparing a suitable 60-carbon precursor and for closing it up to the fullerene ball. This review provides a personal account of how the new synthetic tools were developed and put to use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
127
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(132 citation statements)
references
References 115 publications
1
127
0
4
Order By: Relevance
“…The corresponding precursor molecule can be transformed into the desired nanostructure by consecutive intramolecular aryl-aryl coupling. [5] Formally, this approach can be applied to the synthesis of any conceivable nanostructure without limitations, as soon as highly selective aryl-aryl coupling techniques are available. The most powerful method known to date is flash vacuum pyrolysis (FVP), [6] which has proven effective for the synthesis of various small buckybowls.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding precursor molecule can be transformed into the desired nanostructure by consecutive intramolecular aryl-aryl coupling. [5] Formally, this approach can be applied to the synthesis of any conceivable nanostructure without limitations, as soon as highly selective aryl-aryl coupling techniques are available. The most powerful method known to date is flash vacuum pyrolysis (FVP), [6] which has proven effective for the synthesis of various small buckybowls.…”
mentioning
confidence: 99%
“…The most powerful method known to date is flash vacuum pyrolysis (FVP), [6] which has proven effective for the synthesis of various small buckybowls. [5] However, a high-yield synthesis of isomerically pure fullerenes by FVP has not yet been realized. [7] Alternatively, an effective intramolecular aryl-aryl coupling can be achieved by surface catalyzed cyclodehydrogenation.…”
mentioning
confidence: 99%
“…The high temperature applied in FVP causes hemolytic cleavage of C─H bonds leading to the formation of radicals possessing enough energy to cause intramolecular cyclization yielding highly strained products. Pioneering by Scott et al, variety of small bowl-shaped PAHs (fullerene fragments) have been successfully synthesized in macroscopic amounts via intramolecular cyclization of quasi-planar PAH precursors under FVP conditions [40][41][42]. It was found that introduction of chlorine or bromine functionalities into the initial precursor is essential to facilitate the cyclization via free radical mechanism (Figure 9).…”
Section: Gas Phase Synthesismentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] In this series triphenylenes [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] and their thiophene analogues (viz. phenanthro [9,10- A first-rate review on the chemistry of the above mentioned heteroaromatic systems, focusing on their synthesis, electronic properties, and applications in materials science, has recently been published.…”
Section: Introductionmentioning
confidence: 99%